Russia against Europe: A clash of interpretations of modernity?. (November 2019) - Maslovskiy, Mikhail
This article argues that combining elements of the sociological theories of Johann Arnason and Peter Wagner can contribute to an understanding of the causes of the 'new Cold War' on the European continent. Comparisons of today's confrontation between Russia and the West with the original Cold War are largely misleading since the Soviet model of modernity represented a radical alternative to its liberal western version. Unlike the original Cold War, the current ideological confrontation is not connected with a clash of different forms of modernity. Today's Russia lacks a clear civilizational identity and does not follow an alternative project of modernity. The recent 'conservative turn' in Russian politics largely draws on a specific interpretation of European modernity.